Blocking of the CXCR4-CXCL12 Interaction Inhibits the Migration of Chicken B Cells Into the Bursa of Fabricius - Laparidou, Maria; Schlickenrieder, Antonina; Thoma, Theresa; Lengyel, Kamila; Schusser, Benjamin (Frontiers in Immunology, 2020)
B cells have first been described in chickens as antibody producing cells and were named after the Bursa of Fabricius, a unique organ supporting their development. Understanding different factors mediating the early migration of B cells into the bursa of Fabricius is crucial for the study of B cell biology. While CXCL12 (stromal derived factor 1) was found to play an important role in B lymphocyte trafficking in mammals, its role in the chicken is still unknown. Previous studies indicated that chicken CXCL12 and its receptor CXCR4 are simultaneously expressed during bursal development. In this study, we investigated whether the CXCR4/CXCL12 interaction mediates B cell migration in chicken embryo. We used the CRISPR/Cas9 system to induce a CXCR4 knockout in chicken B cells which led to chemotaxis inhibition towards CXCL12. This was confirmed by adoptive cell transfer and inhibition of the CXCR4/CXCL12 interaction by blocking with the small inhibitor AMD3100. In addition, we found that the chicken exhibits similarities to mice when it comes to CXCR4 being dependent on B cell receptor expression. B cells lacking the B cell receptor failed to migrate towards CXCL12 and showed no response upon CXCL12 stimulation. Overall, we demonstrated the significance of CXCR4/CXCL12 in chicken B cell development in vivo and the importance of the B cell receptor in CXCR4 dependent signaling.